Brain exposure of osimertinib in patients with epidermal growth factor receptor mutation non‐small cell lung cancer and brain metastases: A positron emission tomography and magnetic resonance imaging study - Ekman, Simon; Cselényi, Zsolt; Varrone, Andrea; Jucaite, Aurelija; Martin, Heather; Schou, Magnus; Johnström, Peter; Laus, Gianluca; Lewensohn, Rolf; Brown, Andrew P.; Aart, Jasper; Vishwanathan, Karthick; et al. (Clinical and translational science, 2023)
Brain metastases (BMs) are associated with poor prognosis in epidermal growth factor receptor mutation‐positive (EGFRm) non‐small cell lung cancer (NSCLC). Osimertinib is a third‐generation, irreversible, EGFR‐tyrosine kinase inhibitor that potently and selectively inhibits EGFR‐sensitizing and T790M resistance mutations with efficacy in EGFRm NSCLC including central nervous system (CNS) metastases. The open‐label phase I positron emission tomography (PET) and magnetic resonance imaging (MRI) study (ODIN‐BM) assessed [11C]osimertinib brain exposure and distribution in patients with EGFRm NSCLC and BMs. Three dynamic 90‐min [11C]osimertinib PET examinations were acquired together with metabolite‐corrected arterial plasma input functions at: baseline, after first oral osimertinib 80 mg dose, and after greater than or equal to 21 days of osimertinib 80 mg q.d. treatment. Contrast‐enhanced MRI was performed at screening and after 25–35 days of osimertinib 80 mg q.d.; treatment effect was assessed per CNS Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 and per volumetric changes in total BM using a novel analysis approach. Four patients (aged 51–77 years) completed the study. At baseline, ~1.5% injected radioactivity reached the brain (IDmax[brain]) 22 min (median, Tmax[brain]) after injection. Total volume of distribution (VT) in whole brain was numerically higher compared with the BM regions. After a single oral osimertinib 80 mg dose, there was no consistent decrease in VT in whole brain or BMs. After greater than or equal to 21 days' daily treatment, VT in whole brain and BMs were numerically higher versus baseline. MRI revealed 56%–95% reduction in total BMs volume after 25–35 days of osimertinib 80 mg q.d. treatment. The [11C]osimertinib crossed the blood–brain and brain‐tumor barriers and had a high, homogeneous brain distribution in patients with EGFRm NSCLC and BMs.